Validation of instrumentation to monitor dynamic performance of Olympic weightlifters - Bruenger, A. J.; Smith, S. L.; Sands, W. A.; Leigh, M. R. (The Journal of Strength and Conditioning Research, 2007)
The purpose of this study was to validate the accuracy and reliability of the Weightlifting Video Overlay System (WVOS) used by coaches and sport biomechanists at the United States Olympic Training Center. Static trials with the bar set at specific positions and dynamic trials of a power snatch were performed. Static and dynamic values obtained by the WVOS were compared with values obtained by tape measure and standard video kinematic analysis. Coordinate positions (horizontal [X] and vertical [Y]) were compared on both ends (left and right) of the bar. Absolute technical error of measurement between WVOS and kinematic values were calculated (0.97 cm [left X], 0.98 cm [right X], 0.88 cm [left Y], and 0.53 cm [right Y]) for the static data. Pearson correlations for all dynamic trials exceeded r = 0.88. The greatest discrepancies between the 2 measuring systems were found to occur when there was twisting of the bar during the performance. This error was probably due to the location on the bar where the coordinates were measured. The WVOS appears to provide accurate position information when compared with standard kinematics; however, care must be taken in evaluating position measurements if there is a significant amount of twisting in the movement. The WVOS appears to be reliable and valid within reasonable error limits for the determination of weightlifting movement technique.